Musculoskeletal pain and posture decrease step length in young adults - Rachmawati, Maria Regina; Samara, Diana; Tjhin, Purnamawati; Wartono, Magdalena; Bastian, Yefta (Universa Medicina, 2009)
Pain of the musculoskeletal system, especially low back pain, is one of the most frequent problems with a high risk of disability. The aim of this research study was to determine the existence of an association between low back pain on one hand,Â  posture and step length on the other. This cross-sectional study was conducted on 77 healthy young adult subjects. Step length was measured with the Biodex Gait Trainer 2 (230 VAC). The study results indicate that 62.3% of the young adult subjects had suffered from low back pain. There was no significant association between gender and pain. In male subjects no significant association was found between pain on one hand and mean difference in step length and posture on the other. However, in female subjects with abnormal posture, there was a highly significant difference in left step length between subjects with back pain and those without (p=0.007).Â  The results of a multiple regression analysis indicate that posture has the greatest influence on left step length (B=4.135; 95% Confidence Interval 0.292-7.977). It is recommended that in the examination of low back pain an assessment be made of posture, step length and difference in step lengths.